Meaningful Didactic Reflections Stemming from a Curricular Management Model for Initial Teacher Training in the Context of a Pandemic and Virtuality [Reflexiones Didácticas Con Sentido a Partir de Un Modelo de Gestión Curricular Para la Formación Inicial Docente en Contexto de Pandemia y Virtualidad] - Fernandez-Vergara, O; Poblete-Galvez, C (Universidad Austral de Chile, 2022)
One of the great challenges presented by undergraduate training is to demonstrate the institutional educational model in coherence with national policies and quality standards in higher education through verifiable actions in a context of virtuality and pandemic. This work is based on the analysis of an action research project that had two defining moments: the first, to recognize the socio-cultural particularities of the participating educational community about the didactic ways of solving the challenge of initial formation and a second moment of implementation of a non-parametrical didactic proposal from the methodology of teaching in the context of virtual education and the pandemic. New challenges arise from this that point to the unexplored complexity of these didactic approaches in the initial training of teachers and their usefulness and coherence to collect evidence © 2022, Estudios Pedagogicos.All Rights Reserved.